Phenyl trimethyl ammonium tribromide mediated robust one-pot synthesis of spiro-oxacycles – an economic route – stereoselective synthesis of oxaspirohexacyclodieneones. Issue 33 (1st August 2016) - Sarkar, Debayan; Ghosh, Manoj Kumar; Rout, Nilendri
Abstract : This paper entails the first recognition of Phenyl Trimethyl Ammonium Tribromide (PTAB) as an effective reagent for spiro-cyclizations proceeding via oxidative dearomatization. Abstract : This paper entails the first recognition of Phenyl Trimethyl Ammonium Tribromide (PTAB) as an effective reagent for spiro-cyclizations proceeding via oxidative dearomatization. The experiment exhibits economical, metal and ligand free one-pot accomplishment of these significant transformations. The described protocol presents the first generalised methodology of spiro-oxacycle synthesis which can be applied towards various directions. A stereoselective synthesis of oxa-spirocyclooxadieneones has been accomplished.